A Journey toward Immediate Denture: Overcoming Bitter Reality with Psychotherapy - R. Varsha; P. S. Manoharan; Vigneshvar Chandrasekaran; K. Savitha (Hindawi Limited, 2022)
The loss of teeth affects the aesthetics, function (mastication and speech), confidence, mental state, and the overall quality of life of an individual. Aggressive periodontitis is a destructive condition leading to loss of teeth at early stages of the disease. Individuals facing this inevitable condition of losing the teeth and replacement at a younger age experience formidable psychological distress. The prosthodontic procedure when supported with psychotherapeutic interventions can support the patient in accepting the prognosis and treatment. We report the scenario where psychological intervention was provided in a systematic manner adopting the SPIKES protocol for a 42-year-old man presenting with aggressive periodontitis.